Mathematics in Nature : Modeling patterns in the natural world - John A Adam (Universities Press, 2005)
The confluence of nature and mathematical modeling -- Estimation : the power of arithmetic in solving Fermi problems -- Shape, size, and similarity : the problem of scale -- Meteorological optics I : shadows, crepuscular rays, and related optical phenomena -- Meteorological optics II : a "calculus I" approach to rainbows, halos, and glories -- Clouds, sand dunes, and hurricanes -- (Linear) waves of all kinds -- Stability -- Bores and nonlinear waves -- The Fibonacci sequence and the golden ratio -- Bees, honeycombs, bubbles, and mud cracks -- River meanders, branching patterns, and trees -- Bird flight -- How did the leopard get its spots?